2016
DOI: 10.12688/wellcomeopenres.10036.1
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic mycobacteria achieve cellular persistence by inhibiting the Niemann-Pick Type C disease cellular pathway

Abstract: Background. Tuberculosis remains a major global health concern. The ability to prevent phagosome-lysosome fusion is a key mechanism by which intracellular mycobacteria, including Mycobacterium tuberculosis, achieve long-term persistence within host cells. The mechanisms underpinning this key intracellular pro-survival strategy remain incompletely understood. Host macrophages infected with persistent mycobacteria share phenotypic similarities with cells taken from patients suffering from Niemann-Pick Disease Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 73 publications
2
29
0
Order By: Relevance
“…In conclusion, as NPC1 is a lipid storage disease the use of a lipidated vehicle may not be the best approach due to the possibility that the additional lipid load could alter metabolism or endocytosis and lead to further lipid storage as we have observed. Based on our evidence 2 , from this report and from others 13,14,28,29 it is perhaps the least modified forms of curcumin that appear to have the greatest benefit for NPC1 disease both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In conclusion, as NPC1 is a lipid storage disease the use of a lipidated vehicle may not be the best approach due to the possibility that the additional lipid load could alter metabolism or endocytosis and lead to further lipid storage as we have observed. Based on our evidence 2 , from this report and from others 13,14,28,29 it is perhaps the least modified forms of curcumin that appear to have the greatest benefit for NPC1 disease both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 64%
“…Unformulated curcumin has been shown to be able to ameliorate NPC disease in five separate studies 2,13,14,28,29 , whilst curcumin formulated into a lipidated vector has been shown to have little to no benefit 13 . The aim of the present study was therefore to determine whether formulated lipidated curcumin could mediate any benefit in NPC1 disease cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, azithromycin has been shown to block the acidification of the phagosomes containing mycobacteria, allowing the latter to escape the phagosome and multiply uncontrollably [58]. However, unlike mycobacteria, which require intact lysosomal function for containment of the infection [59,60], SARS-CoV-2, as discussed earlier, relies on an intact lysosomal function for complete entry and fusion. Thus, it is reasonable to expect that azithromycin would show efficacy against COVID-19, through a similar mechanism to chloroquinethat is, disrupting the function of lysosomal proteases.…”
Section: Making the Link Between Covid-19 And The Lysosomes Based On mentioning
confidence: 99%
“…Cholesterol has been identified as important in the infection process of M. tuberculosis (Peyron et al, ; Ouellet et al, ; Crowe et al, ; Lovewell et al, ; Fineran et al ., ) and is used as a carbon source during survival within macrophages (Van der Geize et al, ; Pandey and Sassetti, ; Rohde et al, ). In previous work, we demonstrated that an operon consisting of hsaA (Rv3567), hsaB (Rv3570), hsaC (Rv3568), hsaD (Rv3569) (Van der Geize et al, ) is involved in cholesterol metabolism.…”
Section: Introductionmentioning
confidence: 99%